Analisis Efektivitas Sistem Manajemen Persuratan Dalam Meningkatkan Kinerja Organisasi - Darmansah, Tengku; Alamsyahdana, Azwar; Pras, Jogi; Silalahi, Khairul Amri (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research aims to analyze the effectiveness of the correspondence management system in improving organizational performance. The research results show that the implementation of this system significantly increases the efficiency of the administrative process, reduces the time required for mail management, and increases the accuracy and precision of information distribution. Apart from that, the correspondence management system also contributes to increasing transparency and accountability in document management. These findings indicate that the use of information technology in correspondence management can be an effective tool in supporting overall organizational performance.